Lateral and torsional stiffness of grid type water tower staging - Khandeshe, Abhay; Ingle, R.K. (Journal of Structural Engineering, 2025)
Water towers with grid type of staging are nowadays more popular in comparison with Intze shape shaft type staging due to non-availability of skilled workers at remote places, costly centering and relatively ease of construction. For seismic as well as dynamic wind analysis, the value of fundamental time period or frequency of the staging is required, which either can be calculated using any standard software or an approximate formulae to calculate stiffness which can be used to evaluate the time period or frequency. Simple expressions for calculation of lateral stiffness due to bending and axial deformation of column as well as torsional stiffness for three typical cases of such staging consisting of four, nine, and twelve columns are proposed, which in turn can be used for calculation of time periods of staging. Simple yet reasonably accurate formulae are worked out and they are verified with the results of Finite Element Analysis (FEA). Three dimensional behavior of towers with relatively flexible braces as compared to strong columns is reasonably accounted for in the procedure followed. Expressions for nine column staging can be very well applied with little modifications to square grids having 16, 25, 36 number of columns. Twelve columns expressions can be used for staging with 21, 24, 32, 37 number of columns in grid pattern, thus covering practically all grid type staging.